An endearing epistle from a dutch colonial governor to a Malay ruler in His Dominion - Che Rodi, Rozita; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2021)
In this article a study is done on the National Library of Malaysia (Perpustakaan Negara Malaysia) MSS 4049 A Letter from A Dutch Colonial Governor-General in Batavia dated 1848 (MSS 4049 Surat daripada Governor General Belanda di Negeri Betawi bertarikh 1848). The study is in the forms of a transliteration, annotation and translation of the letter and also a general discussion of the historical background and content of the letter. Also a discussion on the common features of the Dutch letter with the style of the Malay rulers’ letter will be made, namely the writing of a short formulaic heading on top of the page as a kind of statement, kind words of endearment and honorable words of addressing the recipients, prayer to the Almighty for the long life and good health of the addressee and the mention of the exchange of precious gifts. One feature that is in complete contrast with the etiquette of Malay rulers’ letter writing was the conspicuous introduction in the opening line of the Governor-General’s letter, of the status of the sender with grandeurs mentions of one’s honor and awards, and also the use of plain paper without illumination by the Dutch Governor-General which contrasted to the Malay rulers’ letter writing style of using intricate illumination. This study also revealed that although the letter is from a Dutch colonial Governor-General to one of the Malay rulers in his dominions, the civility, mutual respect and appropriate decorum of addressing between rulers, were practiced and adopted.